Nanotechnologies : concepts, processing and applications - Lacaze, Pierre-Camille. (London : ISTE ; Hoboken, N.J. : Wiley, 2013)
"This book details how successive discoveries of new nanocarbon structures along with progress in different microscopy techniques have caused nanomaterials to take on an increasingly important role in electronics, electrochemical energy storage - batteries and fuel cells - and the electrical conversion of solar energy. Views once seen as futuristic on nanomachines and nanorobotics, therapeutic hopes and medical advances - such as those resulting from the application of new in-situ drug-delivery nanotechniques - are all presented. The most innovative developments are analyzed in terms of applications and should enable the reader to form his or her own opinion about the reality of the progress that can be expected from nanotechnologies in the near future. The book offers background reading for teachers in colleges who wish to have an overview on this subject."--
Concepts, Discoveries and the Rapid Development of Nanotechnologies -- Concepts, Discoveries and the Rapid Development of Nanotechnologies. Nanotechnologies in Context: Social and Scientific Awareness of their Impact / Pierre Camille Lacaze, Pierre-Noel Favennec -- Rapid Expansion of Nanotechnology: New Ways of Observing the Infinitesimal and the Discovery of Carbonaceous Nanomaterials with Unusual Properties, The / Pierre Camille Lacaze, Pierre-Noel Favennec-- Nanomaterials in All their Forms: New Properties Due to the Confinement of Matter / Pierre Camille Lacaze, Pierre-Noel Favennec-- Some Amazing Properties of Nanomaterials and of their Assembly into Networks / Pierre Camille Lacaze, Pierre-Noel Favennec-- Applications and Societal Implications of Nanotechnology -- Applications and Societal Implications of Nanotechnology. Nanoelectronics of the 21st Century / Pierre Camille Lacaze, Pierre-Noel Favennec-- Energy and Nanomaterials / Pierre Camille Lacaze, Pierre-Noel Favennec-- Nanobiology and Nanomedicine / Pierre Camille Lacaze, Pierre-Noel Favennec-- Nanorobotics and Nanomachines of the Future / Pierre Camille Lacaze, Pierre-Noel Favennec-- Conclusions and Outlook.
Includes bibliographical references and indexes.
Print version record.
Keywords: Nanotechnology; SCIENCE -- Nanoscience; TECHNOLOGY & ENGINEERING -- Nanotechnology & MEMS; Nanotechnology; Electronic books